Functional evaluation of LTR-derived lncRNAs in porcine oocytes and zygotes with RNA-seq and small RNA-seq - Yang, Xu; Ji, Jingzhang; Cui, Hongdi; Zhao, Qi; Ding, Chunming; Xu, Chang (Frontiers in Genetics, 2022)
Long noncoding RNAs (lncRNAs) are increasingly being recognized as modulators of early embryonic development in mammals. However, they are seldom investigated in pigs. Here, to annotate full-length RNA transcripts, we performed annotation using a newly developed computational pipeline—an RNA-seq and small RNA-seq combined strategy—using our previously obtained RNA-seq and small RNA-seq data from porcine oocytes and zygotes. As evidenced by the length comparison, the frequency of the core promoter, and the polyadenylation signal motifs, the transcripts appear to be full-length. Furthermore, our strategy allowed the identification of a large number of endogenous retrovirus-associated lncRNAs (ERV-lncRNAs) and found that some of them were highly expressed in porcine zygotes, as compared to oocytes. Through the knockdown strategy, two ERV-lncRNAs (TCONS_00035465 and TCONS_00031520) were identified as playing potential roles in the early embryo development of pigs, laying a foundation for future research.